Genital Hailey- Hailey disease: a case report - Deeptara Pathak Thapa; Anil Kumar Jha; Sujata Pudasaini; Chandani Kharel; Shristi Shrestha (Our Dermatology Online, 2013)
Hailey - Hailey disease is a rare autosomal dominant acantholytic disorder, previously not reported from Nepal. We report a case of 30 years old female who presented with pruritic hyperkeratotic papules and plaques on vulva, perianal area and inner left thigh for a period of one year. Biopsy from the lesion showed suprabasal acantholysis with loss of intercellular bridges resulting in a dilapidated brick-wall appearance; characteristic of Hailey - Hailey disease. Treatment of this disease till date is far from satisfactory.